The Systematic Review and Meta-Analysis on the Immunogenicity and Safety of the Tuberculosis Subunit Vaccines M72/AS01E and MVA85A - Ullah, Inayat; Bibi, Shaheen; Ul Haq, Ijaz; Safia,; Ullah, Kifayat; Ge, Long; Shi, Xintong; Bin, Ma; Niu, Hongxia; Tian, Jinhui; Zhu, Bingdong (Frontiers in Immunology, 2020)
Background: Tuberculosis (TB) is a serious infectious disease worldwide. There is no TB vaccine recommended for use in latent TB infections and healthy adults. M72/AS01E is a new peptide vaccine currently under development, which may improve protection against TB disease. This vaccine has been investigated in several phase I/II clinical trials. MVA85A was one of the viral vector-based subunit vaccine in the clinical trials for TB. MVA85A vaccine has been investigated in several phase I/II clinical trials. Immunogenicity and safety are the first consideration for TB vaccine development. We conducted a meta-analysis to clarify the immunogenicity and safety of M72/AS01E and MVA85A subunit vaccines. Methods: We searched the PubMed, Embase, and Cochrane Library database for published studies (until October 2019) investigating M72/AS01E and MVA85A candidate vaccines. A meta-analysis was performed using the standard methods and procedures established by the Cochrane Collaboration. Results: Eleven eligible studies—involving 4,352 participants—on M72/AS01E and MVA85A candidate vaccines were selected for meta-analysis. The overall pooled proportion of significantly higher abundance of polyfunctional M72/AS01E and MVA85A -specific CD4+ T-cell were 31.61 (95%CI: 12.04, 82.97) and 0.84 (95%CI: 0.01, 1.68) respectively. Which indicated that M72/AS01E and MVA85A had immunogenicity in BCG vaccinated and non-vaccinated population, in HIV-positive and negative population, and even in Mycobacterium tuberculosis infected populations. Compared with the control, participants who received vaccination with M72/AS01E were at increased risk of local injection site redness [relative risk (RR) = 2.64], local swelling (RR = 5.09), malaise (RR = 3.55), and fatigue (RR = 2.16), (RR = 1.59), myalgia (RR = 2.27), and pain (RR = 3.99). The incidences of common adverse events of MVA85A were induration, redness, pain, and headache, etc. The estimation rate of headache, malaise, pain, redness and fever were 0.44, 0.29, 0.72, 0.97 and 0.07 respectively. The findings of meta-analysis showed that M72/AS01E and MVA85A are immunogenic and generally safe in clinical trials. The meta-analysis on the immunogenicity and safety of M72/AS01E and MVA85A vaccine provides some useful information for the evaluation of other subunit vaccines in the clinic.